Comparison of Bentonite Characteristics Before and After be Used as Coagulan of Liquid Tofu Waste - Ayu Yuliana; Risfidian Mohadi; Fitri Suryani Arsyad; Safaruddin Safaruddin (International Journal of Social Service and Research (IJSSR), 2023)
Bentonite obtained from East Java is a Ca-Bentonite type which has been activated with H2SO4 20% based on the XRF results which showed CaO level of 4.15%. Bentonite can be reused after being applied as a coagulant and its based on the results of the Bentonite XRD diffractogram pattern before and after being applied as a coagulant that doesn’t have a significant change of 2q, including the 2q montmorillonite at 21,98? (516,42 cps), 35,47? (384,43 cps), 62,26? (100,66 cps) to 22? (436,22 cps), 35,47? (326,46 cps), 62,79? (65,79 cps) and 2q of quartz (SiO2) at 26,5? (607,56 cps) to 26,53? (537,65 cps). The optimum coagulation conditionsis when height of bentonite is 900 mg in 50 mL of liquid tofu waste pH 2, its can remove turbidity by 98% and TSS by 84.6%.